Pour une approche glocale de la formation des enseignants de langues de spécialité (LSP) au XXIème siècle - Sarré, Cédric (Neofilolog, 2023)
In our globalised world, citizens need to develop increasingly specialised language skills in order to meet the needs of industry. However, the resulting increase in the number of LSP courses to meet this need has not been followed by an increase in the provision of specific training for LSP teachers, as a number of national studies have pointed out. The objective of this article is twofold: first, it aims to find out whether there is a global (international) lack of specific training offered to LSP teachers that could be identified through a large-scale study; secondly, its purpose is to show whether a truly global response to the need for such training is an effective and viable solution. By studying two datasets – a needs analysis and feedback from participants in an LSP Teacher Education MOOC – we show that the lack of specific training in the teaching of LSPs is a global need and that a global response to this need, in the form of a MOOC offering cross-linguistic training applicable to all specialised varieties of all languages, seems to be an effective and viable option, as long as it is able to combine local and global scales, in a resolutely ‘glocal’ approach.